Electrodes: Lithium Intercalation Behavior in Multilayer Silicon Electrodes (Adv. Energy Mater. 7/2014). Issue 7 (May 2014) - Fister, Tim T.; Esbenshade, Jennifer; Chen, Xiao; Long, Brandon R.; Shi, Bing; Schlepütz, Christian M.; Gewirth, Andrew A.; Bedzyk, Michael J.; Fenter, Paul
<x xml:space="preserve">Abstract</x> Silicon multilayers, consisting of alternating layers of amorphous silicon and Cr3Si, combine the charge capacity of silicon with the structural integrity of an intercalation material, as reported by Tim T. Fister and co‐workers in article number 1301494. The heterostructures are found to reversibly expand vertically by a factor of 3.3 during lithiation, while maintaining their layered "crystal" structure, as illustrated in the foreground of the image. The remaining consists of a 3D representation of in situ X‐ray reflectivity data taken during the first cycle of lithiation. The dramatic shift in diffraction peaks during lithiation can be seen in the contour plot of the time‐dependent reflectivity, which is projected below. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>